1995
DOI: 10.1111/j.1600-0714.1995.tb01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the epithelial nuclear‐cytoplasmic ratio and nuclear volume density in human palatal lesions

Abstract: We have analysed both the nuclear-cytoplasmic (N/C) ratio and nuclear volume densities (VVN) in defined strata from human hard palate lesions with and without malignant potential to determine the prognostic reliability and/or validity of this parameter. Measurements of cellular and nuclear areas of basal and spinous cells from normal (N) and pathological palatal epithelium were made on histological sections using an image analyser. The lesions comprised fibrous hyperplasia (FH), traumatic inflammation (INF), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Similar results were found by White, Jin and Yang who found decrease in N/C for fibrous hyperplasias, inflammatory lesions, hyperkeratosis, squamous cell papillomas, lichen planus, leukoplakias with dysplasia and for dysplasias from the edge of malignant lesions as well as in malignant lesions themselves [31]. Another study also showed decrease in the N/C in the risk group than in the normal group, the opposite of what might have been anticipated in the risk lesions.…”
Section: Discussionsupporting
confidence: 67%
“…Similar results were found by White, Jin and Yang who found decrease in N/C for fibrous hyperplasias, inflammatory lesions, hyperkeratosis, squamous cell papillomas, lichen planus, leukoplakias with dysplasia and for dysplasias from the edge of malignant lesions as well as in malignant lesions themselves [31]. Another study also showed decrease in the N/C in the risk group than in the normal group, the opposite of what might have been anticipated in the risk lesions.…”
Section: Discussionsupporting
confidence: 67%
“…We have shown for the first time, to our knowledge, that molecular targeting with ensuing changes in GBM cell morphology may be used to enhance the selectivity of PEFs to induce tumor cell death. Selectivity, regulated by the NCR, opens up the possibility of enhanced targeted cancer therapy, as malignant cells are known to often have increased NCR compared to normal cells (32,33). Because the EphA2 receptor is overexpressed specifically on malignant cells in adulthood, the induced morphology change can be exploited in developing combinatorial targeted therapies using H-FIRE.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the genetic heterogeneity within tumors that acts as a hindrance to most therapies, PEF treatments that target physical characteristics of malignant cells may provide a more effective means of targeting the most malignant sub-populations of such tumors. Cellular morphology, particularly cell size and nuclear-to-cytoplasm ratio (NCR) 26 27 28 , as well as cellular electrical properties 29 are known to differ between normal and tumor cells. We hypothesize that phenotypic characteristics of malignant and normal cells present in the GBM microenvironment vary sufficiently to provide targets for cell-specific ablation with properly tuned PEFs.…”
mentioning
confidence: 99%